2011
DOI: 10.1017/s0317167100012087
|View full text |Cite
|
Sign up to set email alerts
|

Tauopathies: One Disease or Many?

Abstract: Tauopathies are a group of disorders that have in common abnormal accumulation of tau protein in the brain. Although the different tauopathies have long been considered to be separate diseases, it is now clear that progressive supranuclear palsy, corticobasal degeneration and some forms of tau-positive frontotemporal lobar degeneration share clinical, pathological and genetic features. The important overlap between these disorders suggest they may represent different phenotypes of a single disease process, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 112 publications
0
16
0
Order By: Relevance
“…Here, we questioned whether the ExoY ϩ -induced phosphorylated, insoluble tau accumulates outside the cell in a high-molecular-weight form, characteristic of such chronic neurodegenerative tauopathies as Alzheimer's disease (8,48). In our previous work utilizing the Tau-5 antibody to detect total tau and the phosphorylated (Ser 214 ) tau antibody to detect phosphorylated tau, we found no evidence of a highmolecular-weight endothelial tau.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Here, we questioned whether the ExoY ϩ -induced phosphorylated, insoluble tau accumulates outside the cell in a high-molecular-weight form, characteristic of such chronic neurodegenerative tauopathies as Alzheimer's disease (8,48). In our previous work utilizing the Tau-5 antibody to detect total tau and the phosphorylated (Ser 214 ) tau antibody to detect phosphorylated tau, we found no evidence of a highmolecular-weight endothelial tau.…”
Section: Discussionmentioning
confidence: 92%
“…ExoY generates a cyclic nucleotide signature that activates protein kinases A and G, resulting in hyperphosphorylation and insolubility of the endothelial tau (41). In neural disease, tau hyperphosphorylation and insolubility lead to its oligomerization, which is a hallmark of neurodegenerative tauopathies (8,48). However, in previous studies we were unable to detect ExoY-induced tau oligomerization in endothelial cell lysates, an effect that was attributed to phosphorylation at Ser 214 , because tau phosphorylation at this site has been shown to inhibit aggregation (57).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we demonstrate that accumulation of cytosolic cAMP, and not cGMP, leads to large interendothelial gaps and increased permeability in pulmonary microvascular endothelial cells. Because hyperphosphorylated and insoluble Tau are hallmarks of neurodegenerative tauopathies such as Alzheimer disease (30,31), these findings suggest that acute P. aeruginosa infections and chronic neurodegenerative diseases share Tau hyperphosphorylation and insolubility as a common pathophysiological mechanism.…”
mentioning
confidence: 97%
“…The mono clonal antibody we used against the phosphorylated form of tau is not found in normal brain in adults or in immature brain during development. Whereas tauopathies in adults represent several different diseases, each with distinct clinical and neuropathological features, it is suggested that the overlap actually may be different phenotypes of a similar disease process [4]. Perhaps our foetal/infantile tauopathy here described is yet another part of this spectrum.…”
Section: Discussionmentioning
confidence: 84%